The Evolution and the Advantages of MicroED - Nannenga, Brent L.; Bu, Guanhong; Shi, Dan (Frontiers in Molecular Biosciences, 2018)
MicroED is a hybrid method which combines Cryo-EM, electron and X-ray crystallography, and it has been employed to solve many protein crystal structures at atomic or higher resolution. The main doubts of this method for structure determination were the dynamic scattering of electrons, which could cause inaccuracies in amplitude calculations. In this paper, we will discuss the major differences of multiple and/or dynamic scattering effects in protein crystals and inorganic material, and the advantages of continuous rotation vs. precession method. Because the electron diffraction data is the average of hundreds of thousands to a few millions of periodically packed molecules at 100 folds lower dose rate than single particle data collection, we have taken this advantage to assess the radiation damage of a high-energy electron beam on the protein molecules at much lower dose ranges compared to a single particle movie. The evolution of data collection and processing will also be described here in detail.